Antinociceptive Effect of Rat D-Serine Racemase Inhibitors, L-Serine-O-Sulfate, and L-Erythro-3-Hydroxyaspartate in an Arthritic Pain Model - Claudio Laurido; Alejandro Hernández; Teresa Pelissier; Luis Constandil (The Scientific World Journal)
N-methyl-D-aspartic acid receptor (NMDAr) activation requires the presence of D-serine, synthesized from L-serine by a pyridoxal 5′-phosphate-dependent serine racemase (SR). D-serine levels can be lowered by inhibiting the racemization of L-serine. L-serine-O-sulfate (LSOS) and L-erythro-3-hydroxyaspartate (LEHA), among others, have proven to be effective in reducing the D-serine levels in culture cells. It is tempting then to try these compounds in their effectiveness to decrease nociceptive levels in rat arthritic pain. We measured the C-reflex paradigm and wind-up potentiation in the presence of intrathecally injected LSOS (100 μg/10 μL) and LEHA (100 μg/10 μL) in normal and monoarthritic rats. Both compounds decreased the wind-up activity in normal and monoarthritic rats. Accordingly, all the antinociceptive effects were abolished when 300 μg/10 μL of D-serine were injected intrathecally. Since no in vivo results have been presented so far, this constitutes the first evidence that SR inhibitions lower the D-serine levels, thus decreasing the NMDAr activity and the consequent development and maintenance of chronic pain.